Learning Interest in Islamic Religious Education: Examining the Effectiveness of the Synectics, Mind Maps, and Cooperative Learning (SM2CL) Model - Sauwitri, Nadia Eka; Safari; Baharudin (Universitas Islam Negeri Raden Intan Lampung, 2026)
Learning interest in Islamic Religious Education (PAI) remains suboptimal in many Indonesian junior high school contexts, primarily attributable to the dominance of conventional, lecture-based instructional approaches that fail to foster affective engagement and intrinsic student motivation.This study examined the effectiveness of the Synectics, Mind Maps, and Cooperative Learning (SM2CL) integrated model in enhancing seventh-grade students' learning interest—specifically the 'feeling of enjoyment' indicator—in PAI instruction at SMP Negeri 31 Bandar Lampung. A quasi-experimental posttest-only control group design was employed, involving 62 seventh-grade students allocated to an experimental class receiving SM2CL instruction (n = 30, Class VII C) and a control class receiving conventional instruction (n = 32, Class VII D). Data were collected using a validated 15-item learning interest questionnaire (Cronbach's α = 0.842) and subjected to normality (Shapiro–Wilk), homogeneity (Levene), and independent-samples t-test analyses. Statistical analysis revealed no statistically significant difference between the two groups (t = −0.414; df = 60; p = .681), with posttest means of M = 50.60 (SD = 7.70) and M = 51.40 (SD = 7.90) for the experimental and control classes, respectively. Sub-dimensional analysis of the enjoyment indicator similarly yielded negligible between-group differences across all five thematic clusters. Although SM2CL theoretically integrates three complementary pedagogical frameworks—Synectics, Mind Maps, and Cooperative Learning—its implementation in this context did not produce significant gains in students' learning interest. Structural constraints including limited affective readiness, habituation to didactic instruction, and inadequate learning infrastructure are identified as primary moderating factors. These findings contribute to the contextual literature on innovative PAI instruction and underscore the necessity of adaptive implementation strategies.